Extended Hueston Flap: New Solution for Primary Closure - Brambullo, Tito; Dalla Venezia, Erica; Vindigni, Vincenzo; Bassetto, Franco (Journal of Hand and Microsurgery, 2018)
Thumb tip injuries are very common in hand trauma, and several flaps are available to restore the defect. One of them is the Hueston flap. It is very simple and quick to harvest, but it could lead to donor site problems. The variant “radial extended” of this flap, proposed in this article, allows a primary closure of donor site avoiding making scar on contact areas subject to frequent use. We performed this technique in a clinical case that presented a distal thumb amputation with good aesthetic result and satisfactory function.
Keywords: fingertip injury; flap; thumb amputation